PERAN GURU MENGAJI UNTUK ANAK-ANAK DI DESA BONAK DOLOK - Silva Hidayah Nst; Siti Nurhaliza Lubis, Muhammar Hanafi, Ana Yusriah Dalimunthe, Riski Dahliana, Siti Patimah, Rizkina (CV. ADIBA AISHA AMIRA, 2025)
This research aims to assess the extent of the role of Koran teachers towards children in Bonan Dolok village in situations of community service. This research involved various individuals from various communities who were involved in this KKN service effort. The role of a Koran teacher is the same as a teacher at school, except that Koran teachers have a certain schedule which is held based on agreement with parents, which is different from public schools where there is a special schedule. The method used in this research is the Participation Action Research method. The results of this service research show that Koran teachers have a very important role for children, because the presence of Koran teachers can improve children's ability to read the Koran, increase religious and moral development in children, and also increase children's understanding of the Islamic religion. From the data analysis activities carried out there are several things that hinder and implement this Koran teacher. This research also suggests that there should be further steps taken by the community to provide recitation for children.